Identificação molecular de bactérias ácido-láticas e propriedades probióticas in vitro de Lactobacillus spp. isolados de queijo Minas artesanal de Araxá, Minas Gerais - José Givanildo da Silva (2016)
Minas artisanal cheese is made from raw milk added by endogenous starter cultures. During its ripening process, the growth and metabolic activities of lactic acid bacteria (LAB) are important to produce typical flavor and improve cheese safety. Probiotic properties of such LAB against pathogens have been demonstrated. However, few studies describe the microbiota and probiotic potential of LAB isolated from that cheese. This study aimed to molecularly identify LAB present in 84 samples of Minas artisanal cheese produced in Araxá region throughout ripening either at dry or at rainy seasons and evaluate their in vitro probiotic potential. A total of 263 samples of LAB were isolated and 50 of them were identified by the 16S rRNA gene sequencing. The following genus were identified: Lactobacillus (74%), Enterococcus (24%) e Bacillus (2%). From them, ten Lactobacillus samples were selected to be tested by in vitro probiotic potential. Only L. plantarum (C0) was sensitive to all tested antimicrobials. The other samples were resistant to at least one drug. L. plantarum (E5) showed the higher resistance index (60%). Six Lactobacillus samples were resistant to artificial gastric juice, especially L. brevis A6 which showed growth in that medium. L. brevis A6, L. casei B5 and L. plantarum E5 were resistant to bile salts, and the latter showed the lower index of inhibition (20.69%) Only L. brevis (E35) produced hydrogen peroxide. Mean inhibition haloes of Lactobacillus spp. against Enterococcus faecalis ATCC 19433 and L. plantarum C24 were considered different (p0.05). All Lactobacillus spp. samples were able to antagonize the revealed bacteria in the spot-on-the-lawn test. All Lactobacillus spp. samples inhibited pathogens (Escherichia coli ATCC 25922, Salmonella Typhimurirum ATCC 14028 and Shigella flexneri ATCC25875) in co-culture test (p0.0001), except L. plantarum (C0) which did not inhibited S. flexneri. Indeed, there is a high frequency of Lactobacillus spp. among the LAB present in Minas artisanal produced in Araxá region. The majority of them showed in vitro probiotic potential. L. brevis (A6) would be selected to be tested for searching its in vivo probiotic potential and use for cheesemaking as a beneficial microorganism, preserving cheese identity.